A Fourth of July on the Plains - Van Leeuwen, Jean (New York, 1997)
Young Jesse and his family are with a wagon train traveling from Indiana to Oregon when they stop to celebrate the Fourth of July, but Jesse is too young to go hunting with the men so he comes up with his own contribution to the festivities.
easy